The euro at twenty : follies of youth? - Cabral, Ricardo (2019)
This paper overviews the early history of the euro and argues that the euro was suboptimally designed, without monetary sovereignty of Eurozone (EZ) Member States, in order to comply with political goals set by wealthier Member States. Given this constraint, the euro architects designed a single currency in which its irreversibility is achieved through the EZ banking system, with recourse to the TARGET2 payment system. This allowed the banking systems of deficit Member States to fund large cumulative current account deficits in the first decade of the euro. The euro crisis led EZ policy makers to define new far more demanding fiscal rules and a new Banking Union to constrain the ability of EZ banking systems to fund sovereigns and current account deficits. Thus, the euro at twenty has become more fragile.